National Milk Production Dynamics: Interactions Among Dairy Cattle Population, Milk Imports and Exports in Indonesia 2020–2024 - Kefi Amtiran, Chandraone Putra; Alahmad, Ali Omar; Notodiputro, Khairil Anwar; Mualifah, Laily Nissa Atul; Indahwati, Indahwati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
The dairy cattle sub-sector plays a vital role in fulfilling the national demand for animal protein; however, domestic milk production has yet to meet the increasing demand. This study analyzes the impact of dairy cattle population, as well as milk import and export, on milk production in Indonesia from 2020 to 2024. Panel data from various provinces were analyzed using a fixed effects model to identify significant variables. Results indicate that the dairy cattle population has a positive and significant effect on national milk production, with variations across island regions. Conversely, milk import and export showed no significant impact on domestic production. These findings emphasize the importance of region-based development strategies, increasing dairy cattle productivity, and implementing appropriate import protection and substitution policies to enhance national milk production self-sufficiency. This study is expected to provide a basis for policymaking and strategic interventions aimed at sustainable development of the dairy industry.